Androgen receptor (AR) splice variant 7 and full‐length AR expression is associated with clinical outcome: a translational study in patients with castrate‐resistant prostate cancer. (20th September 2019) - Del Re, Marzia; Crucitta, Stefania; Sbrana, Andrea; Rofi, Eleonora; Paolieri, Federico; Gianfilippo, Giulia; Galli, Luca; Falcone, Alfredo; Morganti, Riccardo; Porta, Camillo; Efstathiou, Eleni; van Schaik, Ron; et al.
Abstract : Objectives: To investigate if full‐length androgen receptor (AR‐FL) is associated with resistance to androgen receptor (AR)‐directed therapy independently and/or combined with AR splice variant 7 (AR‐V7). Patients and Methods: Plasma samples were prospectively collected from 73 patients with castrate‐resistant prostate cancer before first‐ or second‐line AR‐directed therapy. mRNA was isolated from exosomes and AR‐FL and AR‐V7 were analysed by droplet digital PCR. Results: AR‐FL was detected in all patients and 22% of them were AR‐V7‐positive at baseline. AR‐FL expression was significantly higher in AR‐V7‐positive vs AR‐V7‐negative patients ( P < 0.0001). After stratifying patients by tertile for AR‐FL expression, progression‐free survival (PFS) was 22 vs 18 vs 4 months for lower vs intermediate vs higher tertile, respectively ( P = 0.0003). The median PFS and overall survival were significantly longer in AR‐V7‐negative vs AR‐V7‐positive patients (20 vs 4 months, P < 0.0001; not reached vs 9 months, P < 0.0001, respectively). Conclusions: Resistance to AR‐directed therapy was associated with the presence of AR‐V7; however, AR‐FL expression may help better refine response and survival of patients to AR‐directed therapy. Both biomarkers, if validated in prospective trials, could be used to select the best treatment strategy.